ONLINE READING MATERIALS TO IMPROVE READING CAPACITY OF THE STUDENTS OF NATIONAL UNIVERSITY OF BATTAMBANG OF CAMBODIA - Nov Sampors; Safnil Arsyad; Dedi Sofyan (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2022)
The Covid-19 pandemic in the world keeps increasing until now. This is the reason that the researcher chose one research related to how the students of the National University of Battambang of Cambodia perceive online reading materials to improve their reading capacity. Mix method was conducted in this research. There were 50 participants joining this research. In quantitative analysis, the participants were asked to answer 63 items of the survey questionnaires with 4 answer options, namely strongly agree, agree, disagree, and strongly disagree. In addition, 21 interview questions were used to conduct qualitative data which were responded by 10 selected interviewees. The results displayed that students had a positive perception of using online reading material. However, they met some problems like facing bad internet connection, having inappropriate electronic devices, experiencing screen light problems, being not able to buy suitable electronic devices to support online reading material, being not good at using suitable terms for searching topics, did not know suitable reading strategies, coming with eyes problem, and concerning about privacy and security. This study pushed students to gain precious knowledge through using online reading material especially, upgrading their reading capacity and achieving their learning goals.